NEW EVIDENCES OF THE LOW-P/HIGH-T PRE-ALPINE METAMORPHISM AND MEDIUM-P ALPINE OVERPRINT OF THE PELAGONIAN ZONE DOCUMENTED IN METAPELITES AND ORTHOGNEISSES FROM THE VORAS MASSIF, MACEDONIA, NORTHERN GREECE - Mposkos, E.; Krone, A. (Bulletin of the Geological Society of Greece, 2004)
Pelitic rocks of the pre-Alpine "gneiss series" from the Voras Massif record a polymetamorphic history of three metamorphic events; a first HT event indicated by migmatitization phenomena, a subsequent LP-HT event (andalusite-sillimanite series) at 2.5-3 Kbar and 610-640°C, and a third medium-P event at ~11 Kbar and ~550°C. The LP-HT metamorphism is associated with intrusion of Variscan granitoid plutois in a magmatic arc setting. The medium-P metamorphism records an Alpine event (probably Early Cretaceous) indicated by kyanite, chlohtoid, garnet and staurolite formation replacing andalusite and cordierite. The Variscan granitoids and the overlying lithologies of the "schist series" are affected only by the medium-P metamorphism. Granitoids are transformed into phengite orthogneisses having the mineral assemblage phen (Si=3.35-3.47 a.p.f.u.)±Bt-Ab-Kfs- Qtz±Czo±Grt and high-alumina pelites into gamet-chloritoid schists with the mineral assemblage Grt-Ctd-Chl-Ms-Qtz-Rt±llm. The "schist series" which underlies the Late Triassic-Early Jurassic marbles and overlies lithologies of the "gneiss series" and metagranitoids represents protoliths of the Permo-Triassic volcanosedimentary series deposited at the eastern margin of the Pelagonian continental block